Radon in groundwater contaminated by dissolved hydrocarbons in Santa Barbara d'Oeste, São Paulo State, Brazil - Galhardi, J. A. [UNESP]; Bonotto, Daniel Marcos [UNESP] (Pergamon-Elsevier B.V. Ltd, 2012)
This investigation reported the Rn-222 activity concentration and dissolved hydrocarbon content in groundwater collected in three gas stations where occurred tanks leaks, in Santa Barbara d'Oeste, São Paulo State, Brazil. The results indicated a tendency of correlation between the radon and BTEX, suggesting that the presence of dissolved hydrocarbons increase the radon concentration in water, due to the preferential partition at this phase. The radiometric data are useful for the detection of residual contamination and dissolved hydrocarbon plumes in groundwater, reinforcing the findings of previous studies held elsewhere. (C) 2012 Elsevier Ltd. All rights reserved.
Keywords: Radon; Groundwater; Contamination; NAPL